2013
DOI: 10.1093/brain/aws354
|View full text |Cite
|
Sign up to set email alerts
|

Damage to ventral and dorsal language pathways in acute aphasia

Abstract: Converging evidence from neuroimaging studies and computational modelling suggests an organization of language in a dual dorsal–ventral brain network: a dorsal stream connects temporoparietal with frontal premotor regions through the superior longitudinal and arcuate fasciculus and integrates sensorimotor processing, e.g. in repetition of speech. A ventral stream connects temporal and prefrontal regions via the extreme capsule and mediates meaning, e.g. in auditory comprehension. The aim of our study was to te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
183
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(210 citation statements)
references
References 51 publications
(70 reference statements)
24
183
1
1
Order By: Relevance
“…One approach to assessing the spatial extent of dual streams is to relate specific measures of speech production or speech comprehension to lesion location in patients (29). However, a limitation of such an approach is that it assumes that the complex aspects of speech production and comprehension can be appreciated with single measures.…”
Section: Significancementioning
confidence: 99%
“…One approach to assessing the spatial extent of dual streams is to relate specific measures of speech production or speech comprehension to lesion location in patients (29). However, a limitation of such an approach is that it assumes that the complex aspects of speech production and comprehension can be appreciated with single measures.…”
Section: Significancementioning
confidence: 99%
“…Temporal tracts, such as the inferior longitudinal fasciculus (ILF), inferior frontal-occipital fasciculus (IFOF), and potentially also the uncinate fasciculus (UF) and middle longitudinal fasciculus, have been shown to be mainly involved in language comprehension (Ivanova et al, 2016;Kümmerer et al, 2013).…”
Section: Diffusion Mrimentioning
confidence: 99%
“…While the MTG generally has been considered a critical region in the language comprehension network, with multiple fibre pathways converging beneath this region and cortical association areas directly connected to it (Turken & Dronkers, 2011), the more anterior portions of the temporal lobe have been described as an amodal conceptual hub (Patterson et al, 2007) and considered a critical region for semantic memory, although its precise function remains unclear (Bonner & Price, 2013). Evidence from the aphasia literature has shown that lesions in the anterior temporal region are associated with semantic recognition and production deficits and that auditory comprehension deficits are associated with a disruption in the ventral stream pathway which connects regions in the temporal and prefrontal lobes (Kümmerer et al, 2013). In terms of concrete and abstract processing specifically and focal aMTG lesions, the literature has shown mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…In aphasia, focal lesions in the anterior temporal region have been associated with semantic recognition and production impairments while disruption of the ventral stream (a pathway connecting regions in auditory cortex with the anterior temporal lobe and prefrontal cortex) results in auditory comprehension deficits (Kümmerer et al, 2013) and a reduction in accuracy in the conduite d'approche (i.e. multiple repeated attempts to retrieve a target)…”
Section: Relationship Between Chronic Brain Activity and Language Recmentioning
confidence: 99%
See 1 more Smart Citation